LEGAL PROTECTION AGAINST THE OWNERS OF INSTAGRAM ACCOUNTS WHICH ARE BUYED SERVICES OF ADDING INSTAGRAM FOLLOWERS - Fitri Lestari; Syarifuddin Syarifuddin; Laili Wahyunita; Tri Hidayati (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2020)
This research is motivated by the buying and selling of Instagram followers who trade accounts without the knowledge and permission of the account owner. Followers of sellers only use a piece of software to make additions, then the Instagram account will automatically add to the Instagram buyer followers account, raising questions about the legal protection of account owners who are traded without permission. This study aims to analyze the legal protection of followers buying and selling transactions. This research uses the documentation method. The results of this study indicate that in the transaction the object being traded is an Instagram account belonging to someone else and without the knowledge of the account owner. If it is examined using repressive legal protection theory, Instagram follower sellers have violated the provisions of article 32 paragraph (1) and (2) so that according to the article, seller followers can be prosecuted by article 48 paragraph (1) and (2) ITE Law. In addition, if reviewed with the theory of preventive legal protection contained in the Regulation of the Minister of Communication and Information Number 20 the Year 2016 Article 2 Paragraphs (1) and (2) as well as the ITE Law in Article 26 paragraphs (1) and (2) this provision contains two basic legitimacy processing of personal data that is based on the consent of the person concerned and on positive legal norms or laws and regulations.